BOOSTING MEMBER WELFARE THROUGH PERFORMANCE, MOTIVATION, AND SHARIA FINANCE IN INDONESIA - Custiana, Custiana; Herlina, Ellin; Halim, Hartanto (PT. Antis International Publisher, 2024)
General Background: Cooperatives play a crucial role in enhancing member welfare, with factors like member performance, work motivation, and financial systems directly influencing outcomes. Specific Background: In Sharia-based cooperatives, the financing system adheres to Islamic principles, providing a distinct framework for assessing its impact on welfare. However, research on the combined effect of these variables in such cooperatives remains limited. Knowledge Gap: Despite the significance of performance and motivation in driving cooperative success, the relationship between these factors and welfare, alongside the role of the Sharia financing system, is underexplored in the cooperative context. Aims: This study aims to analyze the influence of member performance, work motivation, and the Sharia financing system on member welfare in the BMT Anugrah Cooperative, Cirebon. Results: A survey-based quantitative method was employed, with data collected from cooperative members and analyzed using multiple regression. Findings reveal that member performance and work motivation significantly and positively impact welfare. Additionally, the Sharia financing system contributes positively to welfare improvement. Novelty: This study highlights the critical role of the Sharia financing system, alongside performance and motivation, as key drivers of welfare in Sharia-compliant cooperatives, an area that has received limited attention in prior research. Implications: The results suggest that enhancing member performance and motivation, coupled with optimizing Sharia-based financial services, can serve as effective strategies for improving welfare. These insights offer valuable guidance for cooperative management in formulating policies aimed at sustainable welfare improvement in Sharia cooperatives.